Calculation of Morse Potential Parameters of bcc Crystals and Application to Anharmonic Interatomic Effective Potential, Local Force Constant - Hung, Nguyen Van; Hue, Trinh Thi; Duc, Nguyen Ba (VNU Journal of Science: Mathematics - Physics; Vol 31 No 3, 2015)
In this work, Morse potential parameters of bcc crystals have been calculated based on the calculation of volume per atom and atomic number in each elementary cell, as well as the energy of sublimation, the compressibility and the lattice constant. They are used for studying the anharmonic interatomic effective potential, local force constant in XAFS (X-ray Absorption Fine Structure) theory. Numerical results for Fe, W and Mo are found to be in good agreement with experiment and with those of other theories. Keywords: Morse potential parameter, effective potential, local force constant, bcc crystals.